Estado nutricional de um pomar cítrico e influência de fatores ambientes no teor de elementos na folha - Braga, José Mário (Revista Ceres, 2025)
This work describes results of citrus foliar analyses from an orchard on the campus of the Federal University of Viçosa. Analyses were made during three years in order to verify the nutritional status of the orchardand to study the relation of values obtained with respect to solar exposure and finally, to verify if there is a correlation between values of leaf and soil analyses.